The crust-mantle transition beneath Northeast China from P–wave receiver functions - Sebastian, Nita; Tkalčić, Hrvoje; Sippl, Christian; Kim, Seongryong; Reading, Anya M.; Chen, Youlin; Fontaine, Fabrice R. (Frontiers in Earth Science, 2023)
The continental lithosphere of the Northeast China Plain (NECP) is probed using P–wave receiver function analysis of passive seismic data. The NECP is much–discussed as it includes different geological provinces of varying tecto–magmatic origin and dates back from Archean to Holocene. Quantifying the tectonic and magmatic influences on the structure and composition of the lithosphere puts important constraints on evolution of NECP. For this, we explore 89 sites across NECP using receiver function analysis. A recently developed technique of inverting for 1–D S–wave velocity profiles beneath seismic stations that is based on the principles of Bayesian statistics (hierarchical transdimensional Bayesian Inversion; HTBI) is applied to receiver functions from the NECP. In addition, an improved crustal thickness–compressional to shear wave velocity ratio (H–κ) analysis was conducted to retrieve the crustal thickness and Vp/Vs ratio of the region. These estimated point measurements are integrated and systematically studied for a regional view of the current crustal architecture. We observe a laterally varying and highly complex lithosphere beneath the NECP. A shallower crust–mantle transition (<= 32km) characterizes the Precambrian North China craton and Late Mesozoic–Cenozoic Songliao Basin from the adjacent Central Asian Orogenic Belt and the Changbaishan Volcanic field (35–40 km). Beneath the latter, low Vp/Vs ratios (~1.65) are obtained, whereas all other regions feature ratios in excess of 1.75. Multiple velocity gradients are observed at crustal depths within the craton, in contrast to the adjacent orogen, which indicates a higher degree of crustal complexity of the former. The width of the crust¬¬¬–mantle transition across the NECP is found to be mainly intermediate (2–7 km) and occasionally sharp (<=2km). From our observations, we infer that there is a substantial difference between the eastern North China Craton's lithospheric architecture and the rest of the NECP, with most of the NECP exhibiting more complexity than previously reported.